Strategic steps to ward off negative potential during digital campaigns ahead of the Indonesian general election in 2024 - Septianda, M. Ferdi; Kurniawan, Deni (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
Political activities such as general election campaigns in Indonesia have been elaborated on a digital basis. Digital election campaigns place the public as sources or intermediaries, in contrast to campaigns before the digital era which only placed the public as consumers or recipients. Through social media, people are free to support the candidates they want to elect. On the one hand, digital election campaigns are often used as a tool to bring down political opponents in unhealthy ways because, through social media, people are easily propagated so digital election campaigns have the potential to be filled with hoaxes, hate speech, and black campaigns. This research aims to look for strategic steps that can be taken by the government and society so that the digital campaign ahead of the 2024 elections in Indonesia is not filled with hoaxes, hate speech, and black campaigns. This research is qualitative research in the nature of a literature study to collect information relevant to the topic of discussion. The data sources used come from reference books and scientific articles. Before finding strategic steps to counteract the negative potential of digital campaigns ahead of the election, researchers first look for and analyze the factors that underlie the negative potential of digital campaigns ahead of the election. The research results show that four factors underlie the emergence of negative potential for digital campaigns ahead of the election, including ambition for power, political polarization, societal and cultural factors, and digital literacy factors. These factors were analyzed, resulting in four strategic steps that could be taken to counteract the negative potential of digital campaigns ahead of the elections in Indonesia in 2024. First, public education. second, increasing digital literacy. third, supervision and law enforcement. fourth, cooperation between institutions.